Increase Reading Comprehension and Critical Thinking through Reading Stories - Marwan; Fery Muhamad Firdaus; Ida Wuri Handayani (Universitas Pendidikan Ganesha, 2024)
The successful implementation of the teacher's learning process in Indonesian language lessons in elementary schools depends on students' understanding of basic reading and critical thinking skills. The aim of the research is to develop teaching modules in developing students' reading and critical thinking skills (DRTA) models in improving reading and critical thinking from the fourth grade elementary school students. This research was conducted using a descriptive methodology with a combination of development and research (R&D) approaches using the ADDIE design. In carrying out this research, data collection techniques were used which included defining the early stages of module development and prototype design, as well as preparing the module draft. Data collection through interviews, observation, documentation, and literature studies. The data analysis technique used is descriptive statistical analysis technique and inferential statistical analysis of research findings showing a significant increase in various fields among grade 4 students with a total of 25 students. In particular, there was a significant improvement in their ability to initial reading ability material and think critically by applying DRTA. Thus the DRTA model can improve the ability to think, read, understand and think critically.